2009
DOI: 10.4012/dmj.28.501
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and cytotoxicity of experimental soft lining materials based on urethane acrylate oligomers

Abstract: The purpose of this investigation was to determine whether experimental light-curing soft lining materials (ESLMs) based on commercially available urethane acrylate oligomers (UA-160TM, UV-3200B, UV-3500BA, and UV-3700B) are suitable for clinical use by measuring their viscosity, compressive modulus, Shore A hardness, tensile strength, adhesive strength, and cytotoxicity. The viscosities of the four ESLMs at 25°C were 10.5 Pa•s, UV-3500BA; 144.0 Pa•s, UA-160TM; 328.8 Pa•s, UV-3700B; and 1079.7 Pa•s, UV-3200B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
0
13
0
5
Order By: Relevance
“…Kanie et al [15] evaluated different soft lining materials based on urethane acrylate oligomers and observed that all of them showed high cell viability.…”
Section: Polymerization Methodsmentioning
confidence: 99%
“…Kanie et al [15] evaluated different soft lining materials based on urethane acrylate oligomers and observed that all of them showed high cell viability.…”
Section: Polymerization Methodsmentioning
confidence: 99%
“…Although silicone elastomers have been widely used as a permanent soft lining material due to their excellent elastic properties, they still have low cushioning effect, low tear strength and are susceptible to deterioration in the oral environment. Therefore, many studies have been conducted to improve existing materials or to develop new materials for use as permanent denture soft lining materials [6][7][8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Silicone elastomers have widely been used as permanent soft lining materials due to their excellent elastic properties; however, they have low cushioning effect, low tear strength and are susceptible to deterioration in the oral environment. Many studies have been conducted to improve the properties of existing silicone materials or to develop new materials for use as permanent denture soft liners [3][4][5][6][7][8][9] . To enhance the mechanical properties of the silicones, one practical method is an incorporation of hydrophobic surface-treated silica filler with a small particle size and high surface area into silicone matrix.…”
Section: Introductionmentioning
confidence: 99%